2006
DOI: 10.1289/ehp.8030
|View full text |Cite
|
Sign up to set email alerts
|

Water Manganese Exposure and Children’s Intellectual Function in Araihazar, Bangladesh

Abstract: Exposure to manganese via inhalation has long been known to elicit neurotoxicity in adults, but little is known about possible consequences of exposure via drinking water. In this study, we report results of a cross-sectional investigation of intellectual function in 142 10-year-old children in Araihazar, Bangladesh, who had been consuming tube-well water with an average concentration of 793 μg Mn/L and 3 μg arsenic/L. Children and mothers came to our field clinic, where children received a medical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
417
11
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 685 publications
(456 citation statements)
references
References 22 publications
18
417
11
10
Order By: Relevance
“…A recent study suggests that high levels of Mn in drinking water ([300 mg/l) are associated with reduced intellectual function (Wasserman et al 2006) and induced neurological disorders similar to Parkinson diseases (Aschner 1997;Lander et al 1999). Recent studies suggest that oxidative stress may play a key role in manganese-induced neurotoxicity (Aschner 1997;Galvani et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggests that high levels of Mn in drinking water ([300 mg/l) are associated with reduced intellectual function (Wasserman et al 2006) and induced neurological disorders similar to Parkinson diseases (Aschner 1997;Lander et al 1999). Recent studies suggest that oxidative stress may play a key role in manganese-induced neurotoxicity (Aschner 1997;Galvani et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies in Bangladesh suggest that ingesting high doses of Mn in drinking water is associated with neurotoxic effects in children, interfering with their intellectual function, as well as causing infant mortality 24,25 . Similar studies have shown that drinking water containing much lower concentrations of Mn than those found in Bangladesh also caused intellectual impairment in school children 26 .…”
Section: Introductionmentioning
confidence: 99%
“…This increased consumption of groundwater, however, has led to long-term population exposure to a wide spectrum of minerals naturally found in aquifers (Kinniburgh & Smedley 2001). For example, in some areas there has been unanticipated exposures to levels of arsenic (Brinkel et al 2009;Rahman et al 2009) and manganese (Wasserman et al 2009) that are consistent with adverse health risks including cancers, cardiovascular disease, diabetes mellitus, hyperkeratosis, pigmentation changes, and kidney, liver, respiratory and neurological disorders (Kapaj et al 2006;Balakumar & Kaur 2009 (Ravenscroft 2003). Two-member teams of field technicians used handheld global positioning system (GPS) units (Garmin E-trex Legend w , Garmin, Kansas) onto which the waypoints, defined by latitude and longitude, for each cell centre had been uploaded and pre-printed paper maps displaying study area boundaries, roads and landmarks (households, government and non-government offices, etc.)…”
Section: Introductionmentioning
confidence: 99%